DIMENSI PSIKOLOGI DALAM ALQURAN (ANALISIS TEKSTUAL TENTANG AYAT-AYAT ALQURAN) - Sri Hartati; Muhamad Rezi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Alquran, as the Holy Book of Moslems, contents all of the guidance for humans in their life. Those guidances are written in global, not in detail. On the other hand, humanity consists of physics and psychics, and all need guidance from Allah in the Holy Qur’an. One of the directions is about psychology that is defined as a science of mental activities of a living organism. According to the Holy Qur’an, there are five terms of psychological aspects, and they are al-nafs, al-aql, al-qalb, al-ruh, and al-fithrah. All of these we call them the inner dimensions of human or psychology. Each of these aspects has a similarity to understand psychology. But in other case has different meaning and function.